Teaching Augustine (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
In October 2014, more than fifty scholars gathered at Samford University for Augustine Across the Curriculum, a conference designed to help non-specialists teach Augustine more effectively in undergraduate core and general education courses. This volume includes keynote addresses by Peter Iver Kaufman and Kristen Deede Johnson, as well as a selection of top papers from the conference.